Pedagogical bases of using acmeological approach in future teacher’s professional training - Shiraly gizi, Tahirova Shafiga (Universidad y Sociedad, 2023)
The purpuse of this article is to debate the pedagogical basis of using the acmeological approach in the future teacher's professional training highlighting the importance of this approach in improving the quality of professional training of the future teacher. In the article concepts are provided, is explained the pedagogical basis of using the acmeological approach, which plays an important role in increasing the professional competence of the teacher but also attention is down to the fact that there is a special demand for the establishment of a qualitatively different educational system in future teacher training, based on this necessity. The author believes that a student who aims to reach the top of his profession and become a professional can constantly improve his knowledge and skills and develop himself as a creative specialist in the future using this approach. This is notorious today since teachers should make it an important goal to constantly improve not only his knowledge and skills, but also his personal qualities. In this line, the article also shows the factors that a person who wants to become a teacher should pay attention to. Keywords: Acmeology, intellectual and emotional skills, vocational training. RESUMEN El objetivo de este artículo es debatir las bases pedagógicas del uso del enfoque acmeológico en la formación profesional del futuro docente destacando la importancia de este enfoque en la mejora de la calidad de la formación profesional del futuro docente. En el artículo se proporcionan conceptos, se explica la base pedagógica del uso del enfoque acmeológico, que juega un papel importante en el aumento de la competencia profesional del docente, pero también se presta atención al hecho de que existe una demanda especial para el establecimiento de un sistema educativo cualitativamente diferente en la futura formación docente, basado en esta necesidad. El autor cree que un estudiante que aspira a alcanzar la cima de su profesión y convertirse en un profesional puede mejorar constantemente sus conocimientos y habilidades y desarrollarse como un especialista creativo en el futuro utilizando este enfoque. Esto es notorio hoy en día ya que los docentes deben tener como objetivo importante mejorar constantemente no sólo sus conocimientos y habilidades, sino también sus cualidades personales. En esta línea, el artículo también muestra los factores a los que debe prestar atención una persona que quiere convertirse en docente. Palabras clave: Acmeología, habilidades intelectuales y emocionales, formación profesional.